Empowering Mothers in Stimulating Baby Growth and Development - Widowati, Lorensia Panselina; Wardani, Dyah Woro Kartiko Kusumo; Suhaid, Dewi Novitasari; Dewi, Ni Nyoman Sri Artina; Aningsih, Baharika Suci Dwi; Simaibang, Frenta Helena (Universitas Ibn Khaldun, 2024)
One of the most crucial factors is growth, which needs to be treated carefully from a young age. However, parents and medical professionals frequently overlook this. From a young age, a lot of work needs to be done to maximize children's growth and development in order to prevent any unexpected delays or deviations. According to the World Health Organization, the global newborn weight incidence rate is still more than 5% below the recommended level. According to Riskesdas (2018), 33.6% of study participants reported eating difficulties, 44.5% had mild to moderate malnutrition, and 79.2% had had eating difficulties for longer than three months. Massage stimulation is a manual technique that can be used as one of the promotional efforts to overcome children's health issues. A child's brain will be stimulated by appropriate and sufficient stimulation, resulting in the development of motor skills, speech and language, independence and socializing, and behavior and emotions that are ideal for their age. The 2024 study by Wardani et al. on the impact of baby massage on weight gain in infants revealed that there was a correlation between the two, with 52.5% of infants aged 0–3 months who got baby massage gaining more than 1 kilogram each month. The majority of the 111 parents of toddlers who participated in the community service project at St. Matthew the Evangelist Church in Bintaro said they thought the exercise was helpful and would utilize it at home. In light of this, it can be said that this community service project was successful in educating participants about the benefits of massaging infants and toddlers.